Dyshidrotic eczema associated with the use of IVIg - Kotan, Dilcan (BMJ Publishing Group, 2013)
Intravenous immunoglobulin (IVIg) treatment is highly effective for autoimmune diseases including myasthenia gravis. Recovery is observed at approximately. 75% of myasthenia gravis patients through IVIg treatment. As a result of many clinical studies, the recommended dose is determined as 0.4 g/kg for 5 days (maximum total dose at 2 g/kg body weight). If an additional immunomodulatory treatment is not administered, IVIg maintenance treatment is needed mostly. However, some side effects may inhibit long-term treatment. For this reason, it is important to know the effect profile well and when the treatment should be discontinued. A female myasthenia gravis patient case is presented here, where dyshidrotic eczema has occurred after the second dose of  intravenous Ig medication and whose treatment is despite further IVIg therapy.